DAZAP1, an RNA-binding protein required for development and spermatogenesis, can regulate mRNA translation - Smith, Richard W.P. (Cold Spring Harbor Laboratory Press, 2011)
DAZ-associated protein 1 (DAZAP1) is an RNA-binding protein required for normal growth, development, and fertility in mice. However, its molecular functions have not been elucidated. Here we find that Xenopus laevis and human DAZAP1, which are each expressed as short and long forms, act as mRNA-specific activators of translation in a manner that is sensitive to the number of binding sites present within the 3′ UTR. Domain mapping suggests that this conserved function is mainly associated with C-terminal regions of DAZAP1. Interestingly, we find that the expression of xDAZAP1 and its polysome association are developmentally controlled, the latter suggesting that the translational activator function of DAZAP1 is regulated. However, ERK phosphorylation of DAZAP1, which can alter protein interactions with its C terminus, does not play a role in regulating its ability to participate in translational complexes. Since relatively few mRNA-specific activators have been identified, we explored the mechanism by which DAZAP1 activates translation. By utilizing reporter mRNAs with internal ribosome entry sites, we establish that DAZAP1 stimulates translation initiation. Importantly, this activity is not dependent on the recognition of the 5′ cap by initiation factors, showing that it functions downstream from this frequently regulated event, but is modulated by changes in the adenylation status of mRNAs. This suggests a function in the formation of “end-to-end” complexes, which are important for efficient initiation, which we show to be independent of a direct interaction with the bridging protein eIF4G.